2018
DOI: 10.1369/0022155418799957
|View full text |Cite
|
Sign up to set email alerts
|

SCC-S2 Facilitates Tumor Proliferation and Invasion via Activating Wnt Signaling and Depressing Hippo Signaling in Colorectal Cancer Cells and Predicts Poor Prognosis of Patients

Abstract: SCC-S2 overexpression has been implicated in several human cancers, its correlation with prognosis and the mechanism how it reserved biological roles are still uncertain. The current study demonstrated that, in 142 archived colorectal carcinoma (CRC) tissue samples, SCC-S2 expression was significantly correlated with higher histological grade ( p=0.001), tumor invasion ( p=0.001), advanced Dukes staging ( p=0.002), positive regional lymph node metastasis ( p=0.024), and poor overall survival ( p<0.001). MTT (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The results demonstrated that the mRNA levels of TNFAIP8, TIPE1, TIPE2 and TIPE3 in the CRC tissues were significantly lower compared with those in the paired adjacent tissues. Previous studies have demonstrated that the expression of TNFAIP8 protein is upregulated in ~50% of cancer tissues compared with adjacent non-tumor tissue in patients with CRC and is associated with the degree of malignancy of the tumor (34,36). However, it is unclear whether TNFAIP8 isoform a functions in cancer and whether the levels of TNFAIP8 v2 mRNA increases alongside those of TNFAIP8 isoform b in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the mRNA levels of TNFAIP8, TIPE1, TIPE2 and TIPE3 in the CRC tissues were significantly lower compared with those in the paired adjacent tissues. Previous studies have demonstrated that the expression of TNFAIP8 protein is upregulated in ~50% of cancer tissues compared with adjacent non-tumor tissue in patients with CRC and is associated with the degree of malignancy of the tumor (34,36). However, it is unclear whether TNFAIP8 isoform a functions in cancer and whether the levels of TNFAIP8 v2 mRNA increases alongside those of TNFAIP8 isoform b in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo-signaling pathway has been found to be frequently inactivated in multiple human cancer types,9, 10, 11 including CRC 17, 18, 19. Numerous studies have reported that the downregulation of the Hippo pathway components mammalian MST1/2 and LATS1/2 or the upregulation of YAP or TAZ consistently contributed to the inactivation of Hippo signaling, which further promoted the progression of CRC 24, 25, 26.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have shown that the inactivation of Hippo signaling was implicated in various processes of CRC. For example, REGγ contributed to the growth of CRC cells via directly interacting with LATS1, leading to the degradation of LATS1 and inactivation of Hippo signaling; 17 in addition, SCC-S2 overexpression was found to promote the invasion and metastasis of CRC via depressing Hippo signaling 18 . Our previous study demonstrated that the inactivation of Hippo signaling by the overexpression of TFAP2C promoted the progression of CRC via maintaining cancer stem cell-like phenotypes 19 .…”
Section: Introductionmentioning
confidence: 92%
“…Yang et al. confirmed that TIPE can promote tumor proliferation and invasion by activating Wnt signaling and inhibiting Hippo signaling in CRC ( 11 ). Our previous studies showed that TIPE was highly expressed in stage III gastric cancer and was positively correlated with DcR3 and ERK1/2 ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…TIPE has been reported to be overexpressed in colon cancer and to regulate cell proliferation ( 10 ). The latest research shows that TIPE can promote tumor proliferation and invasion by activating Wnt signaling and inhibiting Hippo signaling in CRC cells ( 11 ). Our previous studies showed that TIPE promotes angiogenesis in CRC by regulating VEGFR2 expression.…”
Section: Introductionmentioning
confidence: 99%